(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
In this article, was discussed about melodrama, considering your origin until its presence in the circus-theater. It’s a bibliographic study, with highlight on Italian authors that study the opera as melodrama. In relation to the Brazilian circus-theater, relevant research was cited about its creation and how the melodrama genre is an example of dramaturgy that will predominate in this circus format.